2014
DOI: 10.1016/j.otsr.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Failed subacromial decompression. Risk factors

Abstract: IV (retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In this study, we found that 35.6% (95% CI 26.4–45.8%) of patients still report pain 6 months after surgery. Thus, our findings are in accordance with the results from a retrospective study including 108 patients in which as many as 31 patients (29%) had >3 on a visual analogue scale score 6 months after ASD surgery [24]. Other studies have reported failure rates of 16–25% [4, 5, 712].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that 35.6% (95% CI 26.4–45.8%) of patients still report pain 6 months after surgery. Thus, our findings are in accordance with the results from a retrospective study including 108 patients in which as many as 31 patients (29%) had >3 on a visual analogue scale score 6 months after ASD surgery [24]. Other studies have reported failure rates of 16–25% [4, 5, 712].…”
Section: Discussionsupporting
confidence: 91%
“…We found an association between ongoing insurance case, unemployment, and general tendency to worry (t-STAI) with unexplained persistent pain 6 months after surgery. Previous studies have shown that patients with workers’ compensation have lower shoulder-specific measures (e.g., DASH) and general health measures before and after surgery and have worse outcomes [24, 27, 28]. Even though the underlying factors for the association between a poor outcome and an ongoing insurance case is not fully understood, it is important to be especially aware of patients with ongoing insurance cases.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged recovery and worse outcomes in compensated patients likely leads to more health-care utilization and subsequently higher costs of care after work-related shoulder injuries. 12 - 17 The slow recovery and lower outcome scores would be expected to result in more therapy, potentially more imaging, and more physician office appointments relative to noncompensated patients. The data in this study were generated from large cohorts, with overall health-care costs averaging around US $30 000 by the time the average worker returned to full-time work, with arthroscopy being slightly more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Bouchard et al prescribed some factors for any fail of ASD surgery [20]. We believe there is a much greater chance of success in a decompression performed with meticulous attention to anatomy by placing markers for particular regions (such as a needle inserted in AC joint).…”
Section: Discussionmentioning
confidence: 97%